Study of Simple Harmonic Motion’s Subject Assisted Worksheet Based on MGR with Learning Setting of Poe - Siti Khusnul Khowatim; I Ketut Mahardika; Alex Harijanto (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
This article describes the study of simple harmonic motion subject assisted worksheet based on mathematic and graph representation (MGR) for senior high school with learning setting of POE (Prediction, Observation, Explanation). This study is purposed to describe how is learning of harmonic vibration subject by using learning setting of POE with assisted worksheet based on mathematic and graph representation (MGR). This study uses descriptive research method that describes the qualitative research data in the form of critical analysis of the various sources that have been written by the researcher in relevant research. Sources of information obtained from the data observation result, journals, books, or scientific articles. Steps of writing are collecting data through books, journals, scientific articles, proceedings, the internet, observation, and interviews, then the next step is doing the analysis the data as a process of classification, grouping data, and giving conclusions. The analysis result shows that harmonic vibration subject assisted worksheet based on MGR with learning to set of POE for senior high school can make the learning process more focused and more structured also can increase physics learning activity of students. Harmonic vibration subject has thecharacteristic of the subject that does not require a complicated equation differential, so the extends of subject content by using MGR can be implemented in the balance between physical analysis and mathematic.